2020
DOI: 10.5334/aogh.2776
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Patterns of Animal Bites in the Najafabad, Center of Iran (2012–2017)

Abstract: Introduction Animal bites are a significant public health problem, with the majority of bites coming from dogs, cats and humans. These may presented as punctures, abrasions, tears, or avulsions [1]. In general, animals bite occur as a natural, instinctive behavior, especially when they feel threatened or try to get food. An animal bite can cause infection in victims (in both humans and other animals) [2]. One of the most important diseases transmitted by animal bites is rabies. Rabies is one of the most danger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
7
3
1
Order By: Relevance
“…In the present study, 67% of the animal bites were reported from the rural community, which is consistent with most of the domestic data. However, in a study conducted in Abadeh, 57% of the bitten animal individuals were living in cities, which was not consistent with our study [ 8 , 9 , 11 – 13 ]. This issue can be due to the nature of rural occupations (husbandry and agriculture) as well as the presence of dogs in most rural households in the region.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, 67% of the animal bites were reported from the rural community, which is consistent with most of the domestic data. However, in a study conducted in Abadeh, 57% of the bitten animal individuals were living in cities, which was not consistent with our study [ 8 , 9 , 11 – 13 ]. This issue can be due to the nature of rural occupations (husbandry and agriculture) as well as the presence of dogs in most rural households in the region.…”
Section: Discussioncontrasting
confidence: 99%
“…In a review study conducted in Arab countries, the dog was found as the most important cause of transmitting the virus to humans, with the exception of Oman, where the fox was introduced as the most important cause of transmitting the virus [ 17 ]. In other domestic studies, dog was also reported as the most common bite cause, which was consistent with our study [ 9 , 11 – 13 , 18 ]. This matter can be due to the large presence of dogs as domesticated animals in different human communities with different uses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, most of the bite sites were observed in the hand (27.46%) which was in line with the results of other investigations in this field (Amiri et al, 2020;Janatolmakan et al, 2020). However, in a number of studies, the leg was reported as the most injured member (Abedi et al, 2019;Kassiri et al, 2014a;Sharafi et al, 2016) this difference was due the difference in the anatomic categorization in these studies.…”
supporting
confidence: 91%